2017
DOI: 10.1002/bit.26336
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of cofactor flavin adenine dinucleotide (FAD) synthesis and regeneration in Escherichia coli for production of α‐keto acids

Abstract: Cofactor flavin adenine dinucleotide (FAD) plays a vital role in many FAD-dependent enzymatic reactions; therefore, how to efficiently accelerate FAD synthesis and regeneration is an important topic in biocatalysis and metabolic engineering. In this study, a system involving the synthesis pathway and regeneration of FAD was engineered in Escherichia coli to improve α-keto acid production-from the corresponding l-amino acids-catalyzed by FAD-dependent l-amino acid deaminase (l-AAD). First, key genes, ribH, ribC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…As an important cofactor, FAD plays a key role in many enzymatic reactions. An increased intracellular FAD concentration in E. coli improved the production of phenylpyruvic acid (PPA) [144]. Genes related to the synthesis of FAD, including ribADBHCF, were overexpressed individually to investigate their effects on the intracellular FAD concentration, and the results suggested that reactions catalyzed by ribC (encoding RF synthase), ribF (encoding the bifunctional RFK/FADS) and ribH (encoding lumazine synthase) were the main rate-limiting steps for FAD biosynthesis.…”
Section: Microbial Cell Factories For the Production Of Fadmentioning
confidence: 99%
“…As an important cofactor, FAD plays a key role in many enzymatic reactions. An increased intracellular FAD concentration in E. coli improved the production of phenylpyruvic acid (PPA) [144]. Genes related to the synthesis of FAD, including ribADBHCF, were overexpressed individually to investigate their effects on the intracellular FAD concentration, and the results suggested that reactions catalyzed by ribC (encoding RF synthase), ribF (encoding the bifunctional RFK/FADS) and ribH (encoding lumazine synthase) were the main rate-limiting steps for FAD biosynthesis.…”
Section: Microbial Cell Factories For the Production Of Fadmentioning
confidence: 99%
“…Lee, Park, & Kim, ), in which the overexpression of an oxygen‐carrying protein (bacterial hemoglobin) in an E. coli strain improved the transformation of cyclohexanone into caprolactone. On the other hand, the FAD content of E. coli is roughly estimated to a few µmoles per g CDW (Hou et al, ), namely the same order of magnitude as the production of BVMO (Figure a). As suggested by Milker, Goncalves, Fink, and Rudroff, (), the endogenous FAD maybe not enough to form the active FAD‐bound BVMO, necessary to the reaction.…”
Section: Resultsmentioning
confidence: 94%
“…Regarding the enzyme ratio, another limiting factor probably interfered to explain the plateau observed Figure 4c, possibly the NADPH/NADP + content, O 2 supply, and/or the endogenous FAD content. NADPH limitation is well documented On the other hand, the FAD content of E. coli is roughly estimated to a few µmoles per g CDW (Hou et al, 2017), namely the same order of magnitude as the production of BVMO (Figure 4a). As suggested by Milker, Goncalves, Fink, and Rudroff, (2017), the endogenous FAD maybe not enough to form the active FADbound BVMO, necessary to the reaction.…”
Section: The Effect Of Enzyme Production On Activitymentioning
confidence: 88%
“…Compared to phenylalanine dehydrogenase (Brunhuber, Thoden, Blanchard, & Vanhooke, ; Ödman, Wellborn, & Bommarius, ) and aminotransferases (Hirotsu, Goto, Okamoto, & Miyahara, ), the oxidative deamination reaction l ‐AAD catalyzed requires only one amino acid, and can synthesize PPA without extra addition of coenzyme (FAD) or coenzyme regeneration system, because the FAD E.coli itself produced can support the entire reaction, so l ‐AAD was the optimal one. In addition, Hou et al has obtained the triple mutant D165K/F263M/L336M of l ‐AAD, which produced the highest PPA titer of 10.0 ± 0.4 g·L −1 of resting‐cell biotransformation, with a substrate conversion ratio of 100% (Hou et al, ; Hou, Hossain, Li, Shin, Du, et al, ; Hou, Hossain, Li, Shin, Liu, et al, ). Therefore, the triple mutant of l‐aad was cloned first to generate plasmid pRSF‐aad in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we found that l ‐amino acid deaminases ( l ‐AAD) from Proteus mirabilis KCTC 2566 can catalyze the efficient deamination of l ‐phenylalanine (Phe) to PPA and ammonia with a substrate conversion ratio of 100% (Hou et al, ; Hou, Hossain, Li, Shin, Du, et al, ; Hou, Hossain, Li, Shin, Liu, et al, ). The price of Phe is much lower than that of PPA (the price of PPA is about 500 times that of Phe), and thus the production cost of PLA can be significantly decreased if with Phe, not PPA, is used as the substrate.…”
Section: Introductionmentioning
confidence: 99%